ZBTB17 (MIZ1) Is Important for the Cardiac Stress Response and a Novel Candidate Gene for Cardiomyopathy and Heart Failure. (October 2015) - Buyandelger, Byambajav; Mansfield, Catherine; Kostin, Sawa; Choi, Onjee; Roberts, Angharad M.; Ware, James S.; Mazzarotto, Francesco; Pesce, Francesco; Buchan, Rachel; Isaacson, Rivka L.; Vouffo, Josée; Gunkel, Sylvia; et al.
Abstract : Background—: Mutations in sarcomeric and cytoskeletal proteins are a major cause of hereditary cardiomyopathies, but our knowledge remains incomplete as to how the genetic defects execute their effects. Methods and Results—: We used cysteine and glycine-rich protein 3, a known cardiomyopathy gene, in a yeast 2-hybrid screen and identified zinc-finger and BTB domain-containing protein 17 ( ZBTB17 ) as a novel interacting partner. ZBTB17 is a transcription factor that contains the peak association signal (rs10927875) at the replicated 1p36 cardiomyopathy locus. ZBTB17 expression protected cardiac myocytes from apoptosis in vitro and in a mouse model with cardiac myocyte–specific deletion of Zbtb17, which develops cardiomyopathy and fibrosis after biomechanical stress. ZBTB17 also regulated cardiac myocyte hypertrophy in vitro and in vivo in a calcineurin-dependent manner. Conclusions—: We revealed new functions for ZBTB17 in the heart, a transcription factor that may play a role as a novel cardiomyopathy gene. Abstract : Supplemental Digital Content is available in the text.